To defect or cooperate? investigating gender and cultural differences in prisoner’s dilemma game - Che Roslan, Che Nurul Herdawatti; Mohamad Kadari, Haire; Ninam Shah, Mohd Firdaus; Roslan, Nurul Nadia; Mohd Mahudin, Nor Diana (2014)
The extent to which gender and cultural background interact to influence the level of cooperation was investigated through a game called Prisoner’s Dilemma. Eight Asians (Male = 4; Female = 4) and eight Europeans (Male = 4; Female = 4) university students, who were purposively recruited to participate in the experiment, played 10 trials of an interactive online version of the game. By taking a setting of two prisoners and their negotiations with the investigator to decrease their period of custody in a prison, all participants were informed to make a choice either to ‘defect’ or to remain ‘silent’ in every trial played. Results of a two-way ANOVA showed that there was no significant difference in the level of cooperation between males and females, with F (1, 15) = 3.346, p= 0.092, as well as in the cultural difference between Asian and European students, with F (1, 15) = 0.028, p= 0.871. No interaction was also found between gender and culture, F (1, 15) = 0.000, p= 1.000. These results imply that both male and female students in International Islamic University Malaysia (IIUM) exhibited almost the same level of cooperation, and cultural differences do not seem to influence cooperative interactions between the groups studied. It is likely that religious similarity may proxy for the level of cooperation within a community who shared a religious common ground. Hence, it is suggested that future studies with more diverse participants’ characteristics and larger sample size may bring forth more effective results in examining the potential role of gender and cultural factors on level of cooperation. Besides that, future researchers may modify the content of the test through linguistic equivalence such as back translation and decentered language to reduce anxiety, stress and misunderstanding that can lead to dysfunctional thought processes and behaviors.